A Mathematics Module Based on the 4A Flow (Activity–Analysis–Abstraction–Application) for Improving Trigonometry Learning - Kurniati, Lenny; Kusumawati, Ratih (Journal of Medives : Journal of Mathematics Education IKIP Veteran Semarang, 2025)
This study aims to address a significant gap in the literature regarding the development and implementation of 4A-based trigonometry modules for students from disadvantaged backgrounds. This study employed a research and development approach using the ADDIE model, consisting of five phases: analysis, design, development, implementation, and evaluation. Data collection methods involved interviews with validators, observations of student activities during module implementation, questionnaires administered to both validators and students and interviews with students and the developed 4A learning module. Data collected included quantitative data from module validation and student response questionnaires, as well as qualitative data from validator feedback. Qualitative data were collected using descriptive statistics, while qualitative data were analyzed thematically. Based on the results of this study, it can be concluded that the developed learning module has several advantages. The module can attract students' interest and make learning mathematics more enjoyable, and an attractive and clear module design helps students understand the material. This module can contribute to improving student learning outcomes in mathematics and fostering a more inclusive and equitable learning environment at MA Al Hidayah Semarang.